Antimicrobial and Antioxidant Potential of Silver Nanoparticles Synthesized from Primula vulgaris - Erdem, Belgin; Çiftçi, Harun; Şahin, Yunus Emre (My University, 2022)
In this study, biosynthesis and in vitro phytochemical composition, antibacterial and antioxidant activities of silver nanoparticles were investigated by using aqueous leaf, flower and root extracts of Primula vulgaris (P. vulgaris subsp. vulgaris). The synthesized silver nanoparticles (AgNPs) were confirmed by color conversion and ultraviolet-visible (UV-visible) spectrophotometry. The appearance of a dark brown color and a UV absorption spectrum range at 440 nm confirmed the synthesized silver nanoparticles. The antimicrobial activity of silver nanoparticles synthesized from the leaf of P. vulgaris; S. aureus 25±1, S. epidermidis 20±1, P. aeruginosa 20±1, A. hydrophila 21±1, C. albicans 25±1, C. tropicalis 25±1, C. parapsilosis 22±1 and C. glabrata 20±1 mm zone diameter was determined. The most antimicrobial effect of P. vulgaris leaf aqueous extract; S. aureus 20±1, S. epidermidis 18±1, A.hydrophila 15±1, P. aeruginosa 12±2, C. albicans 18±1, C. glabrata 18±1, C.tropicalis15±2, and C. parapsilosis 15±2 mm zone diameter was revealed. The presence of flavonoids, terpenoids, protein, and carbohydrates was found to be higher in silver nanoparticles synthesized in the flower part of P. vulgaris, according to phytochemical screening. While saponins were detected in P. vulgaris root extracts, tannins and protein were detected in the leaf extract. The flower had the highest total phenolic extract content of the silver nanoparticle (29.08±0 mg GAE/g DW), while the leaf and root had the lowest total phenolic content of 9.06±0.5 and 8.64±3.3 mg GAE/g DW, respectively. The flower had the highest total phenolic extract content of the plant aqueous extracts (25.10±0.2 mg GAE/g DW), while the leaf and root had the lowest (8.28±0.5 and 5.20±0.0 mg GAE/g DW, respectively).The DPPH (1,1-Diphenyl-2-picrylhydrazil) assay was used to assess free radical scavenging activity. The antioxidant activity of AgNPs biosynthesized using P. vulgaris flower extract was 90.6 %, while P. vulgaris flower aqueous extracts were 86.3 %. This can be concluded that silver nanoparticles synthesized using P. vulgaris flower extract are useful in the preparation of pharmacologically useful drugs.